Public expenditures, growth, and poverty: Lessons from developing countries - Fan, Shenggen (International Food Policy Research Institute, 2008)
During the past several decades, developing countries have had mixed results in reducing poverty. While East Asia (particularly China) has achieved astonishing progress in eradicating severe poverty through strong agricultural and overall economic growth, many African countries have experienced an increase in the number of poor. Today, more than 1 billion people still live on less than US$1 per day, and the recent surge in food prices has caused another 100 million people in developing countries to fall into poverty. It is obvious, therefore, that a business as usual" approach is wholly inadequate. In recognition of the fact that persistent poverty and malnutrition result in irreversible costs to human and economic development, developing countries and the international development community have been intensifying their efforts to increase and redirect resources in order to achieve specific development objectives such as the Millennium Development Goals (MDGs). However, public resources are limited, so prioritization is clearly critical. Policymakers want to know what public spending programs have the largest impact on the poor and how the resources should be allocated among different sectors, such as agriculture, infrastructure, health, and education. In recent years, the International Food Policy Research Institute (IFPRI) has conducted numerous studies related to public spending and its impact on growth and poverty reduction. The findings from those studies have been brought together in a new book, Public Expenditures, Growth, and Poverty: Lessons from Developing Countries (published for IFPRI by the Johns Hopkins University Press and, in South Asia, by Oxford University Press). The approach used in the book differs from previous work in that it considers multiple types of government spending, including investments in agriculture, infrastructure, health, education, and social safety nets; recognizes that investments have a direct impact on poverty reduction through multiple channels; and links the effects of public investment to its overall social benefits and cost, using a computable general equilibrium (CGE) framework.